Efficacy of edamame vs. almond consumption on total cholesterol in reproductive-age women - Afina Rachma Sulistyaning; Hesti Permata Sari; Farida Farida; Ellin Evitha Sari; Nona Ariesya Rahma (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2024)
Hypercholesterolemia in adults over 18 years of age poses a significant health risk. Reproductive-age women are susceptible to this condition owing to unhealthy dietary habits, notably consumption of fast food. This study aimed to investigate the potential of edamame and almonds to lower blood cholesterol levels. This study employed a pre-test post-test group design following a 6-week intervention. Twenty-eight participants were recruited through consecutive sampling conducted in Purwokerto between March and August of 2022. Statistical analyses were performed using independent and paired t-tests. Results indicated no significant difference in the effectiveness of edamame and almonds in reducing total cholesterol levels among reproductive-age women (p= 0,534). After consumption of 48,8 g/d edamame for 6 weeks, a substantial decrease in total cholesterol levels was observed (p= 0,004), with a mean reduction of 17,79 ± 19,11 mg/dL. Conversely, the intervention with 42,5 g/d of almonds for 6 weeks did not significantly change total cholesterol levels (p= 0,193), yielding a mean reduction of 11,57 ± 31,51 mg/dL. In conclusion, the consumption of edamame for six weeks is effective in lowering total cholesterol levels among women of reproductive age.